If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(1-3x)=4x+3
We move all terms to the left:
4(1-3x)-(4x+3)=0
We add all the numbers together, and all the variables
4(-3x+1)-(4x+3)=0
We multiply parentheses
-12x-(4x+3)+4=0
We get rid of parentheses
-12x-4x-3+4=0
We add all the numbers together, and all the variables
-16x+1=0
We move all terms containing x to the left, all other terms to the right
-16x=-1
x=-1/-16
x=1/16
| 7k-(k+6)+2k=18 | | 0.33x=21 | | 3/2x=23 | | z=5=25 | | 4(0.5n-3)=n-0.25)(12-8n) | | -8v=10v+6 | | 34r+5-2(3r+4)=7 | | -5×+2y=10 | | x+5/6=2x+1/6 | | 35=1/5a-25 | | (x)^2+(X+2)^2=52 | | 1/3(6x+3)=−2x−5 | | 6x+3+5x+4=0 | | 31 (6x+3)=−2x−531 (6x+3)=−2x−5 | | 2+b=15.7. | | -99=-3(3+6x) | | z-2+z+z+5=5z | | (1/4)r=3r= | | 8+3w=13 | | x+4.50=35.75 | | 4(x-15)+8=20 | | 6(2x-3)=24x-30 | | 3x+4=13x= | | 16z*81z= | | 6(7x+1)=42x-4 | | 3w-4=31 | | -8w=-16/3 | | w4–4=3 | | N-12=n | | -3u/2=9 | | 6(2n+5)=9(7n+9)+9 | | x+5/7=5/10 |